COMPOSITIONS OF THE APATITE-GROUP MINERALS: SUBSTITUTION MECHANISMS AND CONTROLLING FACTORS - Pan Y.; Fleet M.E. (My University, 2002)
The apatite-group minerals of the general formula, M10(ZO4)6X2 (M = Ca, Sr, Pb, Na…, Z = P, As, Si, V…, and X = F, OH, Cl…), are remarkably tolerant to structural distortion and chemical substitution, and consequently are extremely diverse in composition (e.g., Kreidler and Hummel 1970; McConnell 1973; Roy et al. 1978; Elliott 1994). Of particular interest is that a number of important geological, environmental/paleoenvironmental, and technological applications of the apatite-group minerals are directly linked to their chemical compositions. It is therefore fundamentally important to understand the substitution...